Estudo numérico da influência da relaxação da não-linearidade Kerr e aplicações com portas lógicas utilizando PAM em componentes de fibras ópticas : interferômetro de Sagnac e acoplador direcional - Ferreira, Alisson da Conceição (2011)
In this thesis work, the operating characteristics, for two optical devices, Sagnac interferometer (NOLM) and the Symmetric Dual-Core Non-Linear Directional Coupler (NLDC) have been investigated. The first device working with pulses of 10 ps, equivalent to a spectral band width of 0.1 THz, in two different applications: analysis of the nonlinear optical switching with non-instantaneous Kerr effect and the accomplishment of logical gates AND, OR and XOR, under Pulse Amplitude Modulation (PAM). In the second device (with pump pulses of 2 ps and bandwidth of 0,5 THz), NAND, OR and XOR logical gates was investigated, under PAM modulation and under the Cross Phase Modulation (XPM) effect, in a NLDC. The research is carried out through numerical simulations, using the Split-Step method in the first two applications, and of the fourth order Runge Kutta numerical method, in the third application. In the first application, the transmission, compression factor (C) and extinction ratio [XRatio(tr)] curves, versus input energy were analyzed for two lengths of the loop of the NOLM, was investigated. A Very important impact of the relaxation of the nonlinearity in the switching device was observed. In the second application, was found that under the conditions defined of the nonlinear effects, the device behaves in such a way that the resulting behavior has the appearance of logic functions in the Sagnac interferometer, considering GVD and SPM, only. The four possible combinations for two pulses, on the input fibers 1 and 2, modulated by the amplitude (PAM) in the logical levels 0 or 1, were used. The effects of a variation in the coding parameter offset (e ) (of the PAM modulation), in the initial amplitude of the pulse associated to the reference amplitude or unmodulated information, have been investigated and an OR gate, having been emerged. If the phase difference (hence time) between the input pulses is considered, gates AND, OR and XOR were obtained. In the third application, the symmetric dual-core NLDC is submitted to PAM modulation, considering the XPM effect, were examined, as well. The effects of a variation in the coding parameter offset (e ) of the PAM modulation relative to the reference amplitude, was investigated, being obtained an OR gate. The modulated output amplitude versus a phase difference between the input pulses, was also observed, where logical gates NAND, OR and XOR arose.